Using instantaneous cross-correlation coefficients of vibration signals for technical condition monitoring in rotating electric power machines - Hraniak, V.F.; Kukharchuk, V.V.; Kucheruk, V.; Khassenov, А.K. (KSU Publ., 2018)
Proposed in the article is the use of new high-information characteristics, in which capacity we used crosscorrelation coefficients between vibration signals in space-distributed units of a rotating electric machine in combination with amplitudes of vibration signals in the same units. It was theoretically proven that the said characteristics make it possible to restore the information on the amplitudes and spatial localizations of occasional uncompensated disturbing forces, the influence of which gives rise to vibrations during rotating electric machines’ operation. Determined and theoretically substantiated was the duration of vibration signal’s temporal realizations, which is advisable to use when obtaining vibration signals’ cross-correlation coefficients in the units under investigation. It was found that duration of such realizations must be divisible by the frequency of rotation period of electric machine’s rotor. Besides, adapted was the mathematical model for calculation of cross-correlation coefficients taking into account the specificities of origin and the physical nature of vibration signal, which enabled us, having significantly simplified the analytical calculations required for obtaining the cross-correlation coefficients, to calculate cross-correlation coefficients based on measured values of their temporal realizations directly in the real-time mode of electric power machine’s operation. The adequacy of the statements set forth in the article and the informative value of proposed characteristics were proven by way of computerized simulation.
Электрлік айналмалы машиналардың техникалық жағдайын бақылау мониторингі үшін дабыл дірілдерінің өзара корреляциясының мезеттік коэффициенттерін қолдану
Использование мгновенных коэффициентов взаимной корреляции сигналов вибрации для мониторинга технического состояния вращающихся электрических машин
Keywords: measurement; cross-correlation; rotating electric machine; system’s vibration response; rosscorrelation coefficient; uncompensated disturbing force